Towards an Asian structured cable planning model - Dell, Peter (Elsevier Science, 2005)
Organisations may find themselves having to replace cabling after a relatively short period if subsequent communications technologies do not operate over the installed media, resulting in costly disruption. Difficulties predicting which media will be dominant in the future are exacerbated because copper, fibre, and wireless all currently have their proponents. This research identifies factors that will form the basis of a statistical model that could be used to improve media selection decision-making. Further research to develop this model is outlined.